2015
DOI: 10.1155/2015/671705
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stimulation Has a Long-Term Effect on Foreign Vocabulary Acquisition

Abstract: Acquisition of a foreign language is a challenging task that is becoming increasingly more important in the world nowadays. There is evidence suggesting that the frontal and temporal cortices are involved in language processing and comprehension, but it is still unknown whether foreign language acquisition recruits additional cortical areas in a causal manner. For the first time, we used transcranial random noise stimulation on the frontal and parietal brain areas, in order to compare its effect on the acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The delayed behavioural effect produced by tRNS has been extensively reported by numerous studies (Cappelletti et al, 2013;Cohen Kadosh et al, 2010;Dockery et al, 2009;Jones, Gözenman, & Berryhill, 2014;Nitsche et al, 2006;Pasqualotto, Kobanbay, & Proulx, 2015;Snowball et al, 2013). In particular, Cohen Kadosh et al (2010) and Snowball et al (2013) reported that brain stimulation produced a benefit on numeric competence that lasted at least six months.…”
Section: Discussionmentioning
confidence: 81%
“…The delayed behavioural effect produced by tRNS has been extensively reported by numerous studies (Cappelletti et al, 2013;Cohen Kadosh et al, 2010;Dockery et al, 2009;Jones, Gözenman, & Berryhill, 2014;Nitsche et al, 2006;Pasqualotto, Kobanbay, & Proulx, 2015;Snowball et al, 2013). In particular, Cohen Kadosh et al (2010) and Snowball et al (2013) reported that brain stimulation produced a benefit on numeric competence that lasted at least six months.…”
Section: Discussionmentioning
confidence: 81%
“…Besides the classical fronto-temporal language areas, also the parietal lobe—particularly the posterior parietal cortex (PPC)—activated in both bilingual groups. This region is not typically devoted to language, although some studies reported its involvement in the performance of some language tasks (for instance in vocabulary learning, see Pasqualotto et al, 2015). Interestingly, this region is relevant to working memory and its activation might, therefore, reflect the heightened necessity for the bilingual speakers to reinforce and elaborate the linguistic information associated with each language (e.g., Gold et al, 2005; Hartwigsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%